Transcriptome Analysis of a Cotton Cultivar Provides Insights into the Differentially Expressed Genes Underlying Heightened Resistance to the Devastating Verticillium Wilt - He Zhu (MDPI AG, 2021)
Cotton is an important economic crop worldwide. Verticillium wilt (VW) caused by Verticillium dahliae (V. dahliae) is a serious disease in cotton, resulting in massive yield losses and decline of fiber quality. Breeding resistant cotton cultivars is an efficient but elaborate method to improve the resistance of cotton against V. dahliae infection. However, the functional mechanism of several excellent VW resistant cotton cultivars is poorly understood at present. In our current study, we carried out RNA-seq to discover the differentially expressed genes (DEGs) in the roots of susceptible cotton Gossypium hirsutum cultivar Junmian 1 (J1) and resistant cotton G.hirsutum cultivar Liaomian 38 (L38) upon Vd991 inoculation at two time points compared with the mock inoculated control plants. The potential function of DEGs uniquely expressed in J1 and L38 was also analyzed by GO enrichment and KEGG pathway associations. Most DEGs were assigned to resistance-related functions. In addition, resistance gene analogues (RGAs) were identified and analyzed for their role in the heightened resistance of the L38 cultivar against the devastating Vd991. In summary, we analyzed the regulatory network of genes in the resistant cotton cultivar L38 during V. dahliae infection, providing a novel and comprehensive insight into VW resistance in cotton.